2001
DOI: 10.4018/jgim.2001040104
|View full text |Cite
|
Sign up to set email alerts
|

Generic Attributes of IS Graduates

Abstract: This paper describes the final phase of a study that validates a group of generic attributes of graduates of Australian undergraduate degree programs with majors in Information Systems (IS). 105 academics from all Australian universities that offer IS undergraduate degree programs of study and 53 member of the Australian Computer Society (ACS) took part in this study. A three round Delphi questionnaire was used. The results of this study are compared with a previous study of generic attributes conducted by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Part 1 of the instrument identified demography and academic details. Part 2 was a 74 point required skills/capabilities set developed using currently proposed curricula recommendations (Association for Computing Machinery & Association for Information Systems, 1997), and instruments from similar studies (Snoke & Underwood, 1998;Letch & Randolph, 2000;Doke & Williams, 1999;Landry et al, 2000;Morris & Bartczak, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Part 1 of the instrument identified demography and academic details. Part 2 was a 74 point required skills/capabilities set developed using currently proposed curricula recommendations (Association for Computing Machinery & Association for Information Systems, 1997), and instruments from similar studies (Snoke & Underwood, 1998;Letch & Randolph, 2000;Doke & Williams, 1999;Landry et al, 2000;Morris & Bartczak, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Drawing on previous surveys (Cheney, 1988;Cappel, 2001Cappel, /2002Farwell, Lee et al, 1995;Leitheiser, 1992;Leonard, 1999;Snoke & Underwood, 1998a, 1998bTang, Lee et al, 2001;Van Slyke, Kittner et al, 1991) the instrument developed for this study included some additional items in the area of job features and conditions. Items were organised into several sections: demographic data, IS and business computing related skills, non-IS academic subjects, soft skills and personal characteristics, and workplace conditions and incentives.…”
Section: Methodsmentioning
confidence: 99%
“…This equates well with the stated needs of practitioners. Practitioner-based studies (Lee, 2004;Lethbridge, 2000;Trauth, Farwell, & Lee, 1993) and in the Australian context (Scott & Yates, 2002;Snoke & Underwood, 1999;Turner & Lowry, 2003) assist us in building a profile of a practicing IT professional. teaching software Freed (1992) coined the term "relentless innovation" to describe the capacity to invent and implement new ideas that will impact every facet of life.…”
Section: Practicing Softwarementioning
confidence: 99%
“…Snoke and Underwood's (1999) study sampled a wide cross section of the IS academics in Australia, including representatives from all universities offering an undergraduate degree in IS or with a major in IS as of July 1998. It showed that personal and group attributes are consistently more highly valued than technical knowledge competencies.…”
Section: The Australian Perspectivementioning
confidence: 99%